THE CONCEPT OF INTERFAITH MARRIAGE: ISLAM-CATHOLICISM AND ITS IMPLICATIONS FOR THE MORAL EDUCATIONS OF CHILDREN - Emanuel, Fransiskus; Kwirinus, Dismas; Yuniarto, Petrus (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
The focus of this study is to provide an explanation of marriage in Islam and Catholicism and its implications for children's moral education. Interfaith marriages often raise pros and cons in society. Those who disagree think that interfaith marriage violates the rules, so it must be avoided. Meanwhile, for those who agree, consider interfaith marriage as a great gift that must be accepted and lived. In the view of Islam and Catholicism, interfaith marriages are actually permissible and of course follow the rules or provisions of each religion. This theme becomes an interesting topic of discussion in this research. The methods used in this research are the descriptive method and a critical reading of the text. This research does not intend to differentiate between Islamic and Catholic marriages but instead seeks to present Islamic and Catholic views on the concept of interfaith marriage and examine the implications of moral education for children in these two major religions. Islam and Catholicism realize that children are a gift, so they should be formed, educated, and fostered. Parents are primarily responsible for the moral education of their children because from them children learn about life.